Development and Characterisation of Arabinoxylan-Based Composite Films - Salvada, Joana (2022)
UID/AGR/04129/2020. RESOLUTION LAB, an infrastructure at NOVA School of Science and Technology. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.